A Research on Smart Transportation Using Sensors and Embedded Systems (International Journal of Innovative Research in Computer Science & Technology, 2017)
Intelligent transportation systems (ITS) are  advanced applications which, without embodying intelligence  as such, aim to provide innovative services relating to different  modes of transport and traffic management and enable various  users to be better informed and make safer, more coordinated,  and 'smarter' use of transport networks. Highway travel is the  lifeblood of modern industrial nations. The larger roads are  sorely over burdened: around the major cities, heavy usage  slows most peak-hour travel on freeways to less than 60  kilometers per hour. In all excessive traffic causes more than  five billion hours delay every year; it wastes countless gallons  of fuel and needless multiplies exhaust emission. The main goal  of this paper is to make the experience of driving less  burdensome and accident less, especially on long trips. This  can be achieved by making the highway itself part of the  driving experience and integrating roadside technologies that  would allow the overburdened highway system to be used  more efficiently. The automobile will have automatic throttle,  braking and steering control.
Keywords: Overburdened highway system; automatic throttle; braking control; steering control.